2012
DOI: 10.1242/jeb.069559
|View full text |Cite
|
Sign up to set email alerts
|

Developmental phenotypic plasticity in a marsupial

Abstract: SUMMARYClimate change is likely to substantially affect the distribution ranges of species. However, little is known about how different mammalian taxa respond morphologically and physiologically to a rapid change of climate. Our objective was to provide the first quantitative data on the effect of continuous cold exposure during development on morphological and functional variables of a marsupial. Fat-tailed dunnarts (Sminthopsis crassicaudata, Dasyuridae) were reared at an ambient temperature (T a ) of 16°C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…However, heterogeneous nutritional experiences during fetal development may also affect heterothermy among adult mice (Kato et al, 2018). For example, continuous exposure to cold during the development of fat-tailed dunnarts (Sminthopsis crassicaudata) was found to increase heterothermy use among adults (Riek and Geiser, 2012). Between-individual variation in heterothermy could thus reflect a plastic phenotype and, thus, the interaction between genotype and environment as well.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, heterogeneous nutritional experiences during fetal development may also affect heterothermy among adult mice (Kato et al, 2018). For example, continuous exposure to cold during the development of fat-tailed dunnarts (Sminthopsis crassicaudata) was found to increase heterothermy use among adults (Riek and Geiser, 2012). Between-individual variation in heterothermy could thus reflect a plastic phenotype and, thus, the interaction between genotype and environment as well.…”
Section: Resultsmentioning
confidence: 99%
“…But, regardless of whether the heterothermic variation noted reflected individual torpor-use propensity, plasticity, personality or genetic variation as such, continuous among-individual variation in heterothermy supports the specialist-generalist model (Angilletta et al, 2010). Further studies should therefore focus on identifying the variation in animal personality (Menzies, 2010), developmental plasticity (Riek and Geiser, 2012;Kato et al, 2018) or genetic variation that may be responsible for the existence of a specialistgeneralist continuum in thermoregulation strategies. For example, in contrast to other physiological traits that may affect fitness, such as BMR and resting or standard metabolic rate (reviewed in Burton et al, 2011;Pettersen et al, 2018), empirical data about the heritability of heterothermy that would indicate the extent to which it is responsive to natural selection are lacking (Angilletta et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we suggest that the capability for TE can differ among littermates, and further demonstrates that individual variation in TE is influenced by fetal development and ensuing sibling interactions. Riek and Geiser (2012) observed intraspecific plasticity in torpor usage and morphological traits in fat-tailed dunnarts (Sminthopsis crassicaudata) and noted that the differences in torpor usage were affected by the ambient temperature during the rearing period (from birth until adulthood). They suggested that such short-term phenotypic responses without long-term selection are likely to be important for the ability to cope with different climates over a wide distribution range.…”
Section: Discussionmentioning
confidence: 99%
“…Although the plesiomorphic explanation appears more plausible and is also supported by developmental evidence, recent data show that torpor expression in marsupials is not unvarying within a species, but is affected by the environmental conditions of their habitat (Geiser & Ferguson, ), which is likely due to selection, and also is known to occur in placentals (Dunbar & Brigham, ; Zervanos et al ., ; Stawski & Geiser, ). Moreover, short‐term exposure to different temperatures during development can modify torpor expression within one generation (Riek & Geiser, ). Individuals that experience low temperatures during development and growth show more frequent and longer torpor than those raised under warm conditions, demonstrating that torpor expression is subject of developmental phenotypic plasticity.…”
Section: Discussionmentioning
confidence: 99%